**Factorise:**

**(i) 5x**^{2}**– 20xy **

Solution:

= 5x(x – 4y)

**(ii) 2p(x + y) – 3q(x + y) **

Solution:

= (x + y) (2p – 3q)

**(iii) 4(a + b)**^{2}**– 6(a + b) **

Solution:

= 2 (a + b) [2(a + b) – 3]

= 2 (a + b) (2a + 2b – 3)

**(iv) 18x**^{2}**y – 24xyz **

Solution:

= 6xy (3x – 4z)

**(v) 7xa – 70 xb **

Solution:

= 7x (a – 10b)

**(vi) 13m**^{2}**+ 156n**^{2}

Solution:

=13(m^{2} + 12n^{2})

**(vii) 3x**^{2}**+ 6x +6 **

Solution:

= 3 (x^{2} + 2x + 2)

** **

**(viii) 4abx**^{2}**+ 8abx + 120by **

Solution:

= 4ab (x^{2} + 2x +3y)

**Factorise**

**(i) x**^{2}**+ xy + xz + yz **

Solution:

= x (x + y) + z (x+ y)

=(x + y) (x + z)

**(ii) a**^{2}**– ab + ac – bx **

Solution:

= a (a – b) + c (a – b)

= (a – b) (a – c)

(**iii) 4x + bx + 4b + b**^{2}

Solution:

= x (4 + b) + b (4 + b)

= (4 + b) (x + b)

**(iv) 6ax – 6a + 5a – 5 **

Solution:

= 6a (x – 1) + 5 (x – 1)

= (3x + 5) (x^{2} + 1)

**(v) a**^{3}**+ a**^{2}**b + ab + b**^{2}

Solution:

= a^{2} (a +b) + b (a +b)

= (a + b) (a^{2} + b)

**(vi) 3x**^{3}**+ 5x**^{2 }**+ 3x +5 **

Solution:

= x^{2} (3x +5) + 1 (3x + 5)

= (3x + 5) (x^{2} + 1)

**(vii) y**^{4}**– 2y**^{3}**+ y – 2 **

Solution:

= y^{3}(y – 2) + 1 (y – 2)

= (y – 2) (y^{3} – 1)

= (y – 2) (y^{3} – 1^{3})

= (y – 2) (y + 1) (y^{2} – y +1)

**(viii) t**^{4}**+ t**^{4}**– 2t – 2 **

Solution:

= t^{3} (t + 1) – 2(t +1)

= (t – 1) (t^{3} – 2)

5x(x – 4y) = 5×2 – 20xy [ not 5×2 – 2xy]

LikeLiked by 1 person

oh oh that might be typing mistake . Thank you for reminding 🙂

LikeLike